2017
DOI: 10.3126/jkmc.v5i4.18610
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of uremic pruritus in chronic kidney patients undergoing maintenance hemodialysis at Kathmandu Medical College Teaching Hospital

Abstract: Background: Uremic pruritus is a common and troublesome symptom of chronic kidney disease. It is one of the dominant dermatological manifestations of chronic kidney disease which affects the quality of life of patients. Objective: To assess the prevalence and severity of uremic pruritus in chronic kidney disease patients undergoing maintenance hemodialysis. Methodology: A prospective cross-sectional study was done over three months among chronic kidney patients undergoing maintenance hemodialysis to show the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[2830] However, other studies found no association with age of patient and CKD-associated pruritus. [31,32] In our study we found significant association between duration of suffering CKD and CKD-associated pruritus but in literature review we could not find any association between them; however, significant association is reported between CKD-associated pruritus and serum levels of parathormone (PTH), [28,33] blood urea nitrogen (BUN), [28,34,35] serum calcium, [28,36] hyperphosphatemia, [28] hypertension [37] and diabetes. [38] CKD-associated pruritus can adversely affect the medical outcomes and the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2830] However, other studies found no association with age of patient and CKD-associated pruritus. [31,32] In our study we found significant association between duration of suffering CKD and CKD-associated pruritus but in literature review we could not find any association between them; however, significant association is reported between CKD-associated pruritus and serum levels of parathormone (PTH), [28,33] blood urea nitrogen (BUN), [28,34,35] serum calcium, [28,36] hyperphosphatemia, [28] hypertension [37] and diabetes. [38] CKD-associated pruritus can adversely affect the medical outcomes and the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The dialysis equipment was limited in our research, and inadequate dialysis was caused by pressure from too many patients. Similar studies by Adhikari et al revealed the same problem of growing patient numbers and insufficient hemodialysis equipment [23]. The dialysis's increased frequency and duration improve the QOL of individuals, which reduces their odds of death [24].…”
Section: Discussionmentioning
confidence: 70%
“…An earlier study reported the global prevalence of uremic pruritus (moderate or extreme) to be 42%, and also suggested asignificant associa on of uremic pruritus with depression, sleeping disorders, impaired 3 quality of life and death. In Nepal, the prevalence of pruritus among chronic kidney disease pa ents undergoing dialysis 4,5 was es mated to be 40-55%. Even though since long me evidence exists for the rela onship between chronic renal failure and pruritus, its molecular basis remains controversial, considering the subjec ve nature and strong influence of psychological 6 factors.…”
Section: Introductionmentioning
confidence: 99%